The Effect of Transaction Intensity and E-Wallet Promotion Features on Student Personal Financial Management - adriyana nuryadin; Mediaty; Sri Sundari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid growth of financial digitalization has fostered "payment decoupling," a psychological gap between purchasing and actual spending that diminishes financial awareness and encourages impulsive consumption among university students. This research investigates how the frequency of digital transactions and e-wallet promotional incentives influence students' personal financial management, utilizing the framework of Mental Accounting theory. This study adopts a quantitative causal-associative design, analyzing data from 100–150 university students selected via purposive sampling. Multiple linear regression was employed to evaluate the relationship between the variables. The analysis reveals that transaction intensity and promotional stimuli collectively exert a significant impact on financial behavior, where the convenience of digital platforms often undermines effective spending self-regulation. These results highlight the critical necessity for improved digital financial literacy to assist students in mitigating the risks of excessive consumption driven by high-frequency digital access and aggressive marketing tactics.